Chester Barnard's Theory of the Firm: An Institutionalist View. Issue 3 (3rd July 2022) - Valentinov, Vladislav; Roth, Steffen
Abstract: Chester Barnard's work can be shown to contain subversive elements which accord with the spirit of institutionalist scholarship. Barnard saw corporations as systems of power whose sustainability must be backed by moral resources which are becoming increasingly scarce today. This vision suggests that the core role of corporations may be found to be in mobilizing power and morality needed to maintain social cooperation. Even though Barnard failed to develop an adequate critique of corporate power and business enterprise, he advanced a set of innovative concepts which illuminate the contribution of corporations toward the coordination of the social provisioning process.